Characterization of the complete chloroplast genome of Hippophae tibetana - Wu Zhou; Qi Dong; Honglun Wang; Na Hu (Mitochondrial DNA. Part B. Resources, 2020)
Hippophae tibetana adapted well to the unique plateau climate, diffused in the Qinghai–Tibetan Plateau–Himalayas. Here, we characterized the complete chloroplast genome of Hippophae tibetana. The chloroplast genome is found to be 155,810 bp in length with 36.67% GC contents. The chloroplast genome sequences encoding 131 genes, including 85 mRNA genes, 38 tRNA genes, and 8 rRNA genes. The phylogenetic trees further revealed that Hippophae tibetana is an independent species different from the model species Hippophae rhamnoides and chloroplast genome sequence showed a significant variation within and between closely related Hippophae genus.